Synthesis of gold nanoparticles with allicin to modify boron-doped diamond surface for oxygen sensor applications - Raharto, Toto; Setiyanto, Cahya Mukti; Ariyanta, Harits Atika; Nahda, Dinda Prastika Nabila; Hani, Adinda Muthia; Yulizar, Yoki; Ivandini, Tribidasari Anggraningrum; Einaga, Yasuaki (Environmental and Materials, 2023)
Modification of surface of boron-doped diamond (BDD) film with gold nanoparticles (AuNPs) was carried out to increase its catalytic activity for an application as an oxygen sensor. Allicin was isolated from garlic by salting out extraction technique, and then used as the capping agent to synthesize AuNPs as it has a double bond structure that could be reacted to attach the BDD surface under UV light radiation. An average size of AuNPs at around 46,00 ± 9,06 nm was obtained, while the modification of the BDD surface by the synthesized AuNPs indicated that the surface of BDD could be covered by gold at around 0.6 % (w/w). Investigation of the AuNPs-modified BDD as a working electrode for the oxygen reduction by using cyclic voltammograms in 0.1 M phosphate buffer solution pH 7 observed a current peak at around -0.45 V (vs. Ag/AgCl). The current of this peak linearly increased proportionally to the dissolved oxygen concentrations (R2=0.9986). Moreover, a limit of detection of the dissolved oxygen of 0.12 ppm and limit of quantity 0.41 ppm could be achieved with excellent stability at 6.86% RSD with 6 repetitions and sensitivity at 19.086 μA/ppm indicated that the modified BDD is promising for applications as an oxygen sensor.